Variation of Ambient Bioaerosol at The King’s Royally Initiated Laem Phak Bia Environmental Research and Developmental Project, Ban Laem District, Phetchaburi Province - สันติวรพงศ์ ศิริพร; รุ่งรัตนาอุบล ฐิติมา; บัวเลิศ สุรัตน์; จินดามพร อริยา (KKU Science Journal, 2015)
The objective of this research was to investigate the variation of ambient bioaerosol at The King’s Royally Initiated Laem Phak Bia Environmental Research and Developmental Project, Ban Laem District, Phetchaburi Province. The factors of climate and environmental conditions were focused. The air sample with six-stage viable Andersen cascade impactor for 10 minutes at 1, 3 and 7 meter height from aboveground was collected during December, 2013 January and February, 2014. The results showed that the averaged concentrations of microorganisms significantly different statistically. The highest averaged concentration of microorganisms at 1 meter above ground was 1,320.08±30 CFU/m3 and the lowest averaged concentration at 7 meter above ground was 317.23±50 CFU/m3 . It was caused by height, wind speed and solar radiation in the area. In addition, the microorganisms found mainly fungi, including Aspergillus spp., Penicillium spp., Cladosporium spp. and bacteria. The particle sizes of microorganisms were important found in sizes 2.1-3.3 µm. The microorganisms were commonly found in the air.